2013
DOI: 10.1080/00288330.2012.718284
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient distribution and effects on phytoplankton assemblages in the western Korea/Tsushima Strait

Abstract: In this study, we investigated the relationship between seasonal/annual variation in water masses and nutrients, and the effects of nutrients on phytoplankton assemblages in the western Korea/ Tsushima Strait. We collected water samples at least once per month from March 2006 to January 2008. There was seasonal variation in nutrient concentrations, with higher values in winter than in summer, and there was annual variation in chlorophyll-a concentration and phytoplankton abundance during spring, with values be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
2
8
0
1
Order By: Relevance
“…Our study shows the order of brassicasterol > dinosterol > C 37 alkenones (concentrations; both maximum and mean values) and B/∑PB (45%–96%) > D/∑PB (4.3%–50%) > A/∑PB (0–20.77%) in the NEECS‐WTS in summer and autumn. The relatively high values of B/∑PB suggest the dominance of diatoms, consistent with the results in the NEECS‐WTS and adjacent areas in previous studies using small subunit ribosomal RNA pyrosequencing (Boopathi et al, ) and microscopic counting (Guo et al, ; Jang et al, ). For example, Guo et al () studied phytoplankton assemblages in the PN section of the ECS in summer by the Utermöhl method, showing that Bacteriastrum comosum and Chaetoceros decipiens were the dominant diatom species in offshore areas influenced by the Kuroshio intrusion.…”
Section: Discussionsupporting
confidence: 89%
“…Our study shows the order of brassicasterol > dinosterol > C 37 alkenones (concentrations; both maximum and mean values) and B/∑PB (45%–96%) > D/∑PB (4.3%–50%) > A/∑PB (0–20.77%) in the NEECS‐WTS in summer and autumn. The relatively high values of B/∑PB suggest the dominance of diatoms, consistent with the results in the NEECS‐WTS and adjacent areas in previous studies using small subunit ribosomal RNA pyrosequencing (Boopathi et al, ) and microscopic counting (Guo et al, ; Jang et al, ). For example, Guo et al () studied phytoplankton assemblages in the PN section of the ECS in summer by the Utermöhl method, showing that Bacteriastrum comosum and Chaetoceros decipiens were the dominant diatom species in offshore areas influenced by the Kuroshio intrusion.…”
Section: Discussionsupporting
confidence: 89%
“…The mixture of these three types of water could also disturb the lack of a relationship between salinity and nutrient concentration at the salinity maximum. Phytoplankton nutrient consumption can also explain why the mean nutrient concentration of the subsurface maximum (Figure ) is lower than that of the Tsushima Strait bottom water [ Jang et al ., ; Morimoto et al ., ].…”
Section: Discussionmentioning
confidence: 98%
“…Although the relationship between the local oceanic processes and climatic factors has been highlighted, the response of coastal hydrodynamics and marine ecosystems to El Niño is not completely understood 8 10 . For example, the coastal hydrodynamic models included complex interactions between Pacific basin-scale wind forcing and local wind stress in order to predict the seasonal cycle of volume transport, but did not include interannual climate variabilities 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Ref. 10 suggested that the typhoon-dependent nutrient supply largely regulates the abundance and composition of the phytoplankton assemblages. These studies were generally based on short-term (< 2 years) observations rather than long-term monitoring efforts 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation